Harnessing Predictive Analytics: The Role of Machine Learning in Early Disease Detection and Healthcare Optimization - Islam, Md Azharul; Yeasmin, Sumaiya; Hosen, Arif; Vanu, Nur; Riipa, Muslima Begom; Tasnim, Afia Fairooz; Nilima , Sadia Islam (Journal of Ecohumanism, 2025)
Machine learning and predictive analytics are revolutionizing healthcare systems by enhancing early disease detection and optimizing processes. By analyzing vast amounts of data, machine learning models can forecast disease onset before symptoms show up, enabling early intervention in chronic diseases like diabetes, heart disease, and cancer. This capability also helps optimize healthcare resources, enabling hospitals to better manage staffing and resource allocation. The integration of machine learning into standard medical procedures is a paradigm shift that improves preventive care, expedites processes and ultimately results in healthier populations. However, challenges such as data privacy and security need to be addressed for equitable healthcare delivery. Machine learning is revolutionizing early disease detection, overcoming challenges like data privacy, security, transparency, and historical biases, requiring collaboration between medical specialists and data scientists. This research paper explores the use of machine learning in AI-based early disease detection and its potential to predict healthcare prototypes based on detected diseases. Via qualitative analysis from research papers for the last 5 years, the research proceeds to study the role of ML and AI in healthcare. As a result found in the previous research, the advantages in early disease detection, and health care optimization are highly beneficial. Challenges and future of AI, ML and healthcare are also improvised. Machine learning (ML) is revolutionizing healthcare by predicting chronic diseases, improving diagnostic accuracy, and optimizing healthcare delivery. ML models can predict patient admissions, emergency department responses, and personalized medicine. However, challenges like data privacy, security, algorithmic bias, and interoperability must be addressed. Advancements in technology, such as natural language processing and deep learning, are expected to enhance ML models’ capabilities. Collaborative health ecosystems can leverage predictive analytics for improved communication and integrated healthcare delivery.